Do fathers matter? : what science is telling us about the parent we've overlooked - Raeburn, Paul. (New York : Scientific American/Farrar, Straus and Giroux, 2014)
An award-winning journalist and father of five discusses the various stages of fatherhood, revealing the profound physiological connections between children and fathers, from conception through adolescence and into adulthood--and the importance of the relationship between mothers and fathers. In the process, he challenges the legacy of Freud and mainstream views of parental attachment, and also explains how we can become better parents ourselves.
Introduction -- The roots of fatherhood -- Conception: the genetic tug-of-war -- Fathers and pregnancy -- Engagement -- Infants -- Children -- Teenagers -- Older fathers -- What fathers do -- Afterword.
Includes bibliographical references and index.
Keywords: Fatherhood -- Psychological aspects; Father and child; Fathers; Families -- Psychological aspects; Families -- Psychological aspects; Father and child; Fatherhood -- Psychological aspects; Fathers